The influence of students’ problem-solving understanding and results of students’ mathematics learning - Sinaga, Bornok; Sitorus, Jonni; Situmeang, Tiurmaida (Frontiers in Education, 2023)
Problem-solving is the ability to understand issues and steps that will affect students’ mathematics learning results. The research goals are: describing students’ problem-solving understanding and mathematics learning results; testing the influence of gender and grade level on students’ problem-solving understanding and mathematics learning results; and testing the influence of students’ problem-solving understanding on mathematics learning results. The population is all students in the fourth through sixth grades at two primary schools (263 respondents). The sample consists of 244 respondents, with female and male respondents of 123 and 121, and low- and high-grade students of 74 and 170, respectively. The researchers calculated and converted scores into values. Statistical tests were carried out by means of analysis of linear regression and the t-test. The Me of students’ mathematics learning results and problem-solving understanding are 69.679 and 66.889. The female students’ problem-solving understanding Me is greater than male ones’, but male students’ mathematics learning results Me is greater than female ones. The low-grade students’ problem-solving understanding Me is greater than high-grade students, but high-grade students’ mathematics learning results Me is greater than low-grade students. Gender has no influence on students’ mathematics problem-solving understanding or learning results. The grade level has a significant influence on students’ problem-solving understanding but no significant influence on mathematics learning results. The students’ problem-solving understanding has a significant influence on mathematics learning results, with a p value of 0.000. The research findings and results have implications for and contribute to assisting students in processing information and building mathematical knowledge.